Impact of economic internationalization Policies in Colombia, Peru and Chile - Echeverri Romero, Rubén Darío (Cuadernos de Administración, 2020)
In the past four decades, Latin American countries have implemented different trade policies and economic integration models since the 1990s with a structuralist ECLAC approach and then moved on to commercial opening and autonomous integration. The purpose of this document is to analyze how trade policies and integration in Colombia, Chile and, Peru impacted their foreign trade in the period from 1980 through 2017. By using a mixed descriptive methodology, our qualitative approach was based on the documentary analysis of the different Government Plans, identifying three categories: export development, integration agreements, and institutional development. The quantitative approach was descriptive and analyzed the impacts of trade policy on variables such as GDP, exports, trade balance, and export structure per country. It is concluded that trade policies and integration models adopted very similar approaches in these countries. Nevertheless, it was found that Chile and Peru diversified their exports more than Colombia did, thereby improving their international trade.